2010
DOI: 10.1017/s0021859610000328
|View full text |Cite
|
Sign up to set email alerts
|

Effects of betaine supplementation on rumen fermentation, lactation performance, feed digestibilities and plasma characteristics in dairy cows

Abstract: SUMMARYThe objective of the present study was to evaluate the effects of betaine supplementation on rumen fermentation, lactation performance and plasma characteristics in dairy cows. Twenty multiparous Holstein dairy cows (597±11·8 kg body weight (BW), 88±4·5 days in milk (DIM) and average daily milk production of 26·3±0·5 kg/cow) were used in a replicated 4×4 Latin square experiment. The treatments were: control (without betaine), low-betaine (LB), medium-betaine (MB) and high-betaine (HB) with 0, 50, 100 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
63
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(84 citation statements)
references
References 26 publications
(46 reference statements)
17
63
0
Order By: Relevance
“…Supplementation of betaine increased the apparent digestibility of DM, OM, CP, NDF, and ADF, and no effect was observed in EE among the groups during the heat stress condition in dairy cows. The findings of the present study are in line with the previous study of Wang et al [29] who described that dietary betaine improved the digestibility of the nutrients. This may be due to the fact that betaine is an osmolyte and methyl donor, which decreases heat stress, maintains the pH of the rumen, and also improves the ruminal microbial community [30].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Supplementation of betaine increased the apparent digestibility of DM, OM, CP, NDF, and ADF, and no effect was observed in EE among the groups during the heat stress condition in dairy cows. The findings of the present study are in line with the previous study of Wang et al [29] who described that dietary betaine improved the digestibility of the nutrients. This may be due to the fact that betaine is an osmolyte and methyl donor, which decreases heat stress, maintains the pH of the rumen, and also improves the ruminal microbial community [30].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, glucose levels in serum increased with the supplementation of betaine; this may be due to increased feed intake and digestibility in the gastrointestinal tract. Serum NEFA levels can serve as energy balance and energy utilization indicators in cows [29]. In the current study, the linearly decreased NEFA levels in plasma suggest that the availability of energy improved with the supplementation of betaine.…”
Section: Discussionsupporting
confidence: 48%
“…In particular, the milk yield of high producing dairy cows may exhibit a sharp decrease (Wang C et al, 2010;Zimbelman et al, 2010). This phenomenon might be explained by several factors.…”
Section: Discussionmentioning
confidence: 99%
“…Although most studies on betaine as a nutritional supplement have been carried out on pigs and poultry for the purpose of reducing heat stress and improving growth performance, reports for beef have shown that betaine was effective in lowering the incidence of high rigor temperature carcasses (Loxton et al 2007), reducing rectal temperatures under both thermo-neutral and heat-challenging conditions in sheep (DiGiacomo 2011), and reducing heart and respiration rates in sheep (DiGiacomo et al 2012). In addition, Wang et al (2010a) showed that betaine was effective in reducing insulin resistance by decreasing non-esterified fatty acids (NEFA) in dairy cattle; further support for this effect in mice and humans was reported by Wang et al (2010b) and Borgschulte et al (2008). Various mechanisms of the involvement of betaine in thermoprotection and insulin resistance are discussed by DiGiacomo et al (2014).…”
Section: Pre-slaughter Interventionsmentioning
confidence: 90%